Sustainable entrepreneurship: Creating environmental solutions in light of planetary boundaries - Schaltegger, Stefan; Beckmann, Markus; Hockerts, Kai (International Journal of Entrepreneurial Venturing, 2018)
This article discusses sustainable entrepreneurship in light of planetary boundaries and related aims to contribute to managing for and in a safe operating space for humanity. The rapidly developing research area of environmental, social and sustainable entrepreneurship has flourished for the last two decades and improved our understanding of the phenomenon. However, while a contribution to sustainable development is often stated in general terms or implied, most of the sustainable entrepreneurship literature focuses on classifications, motivations, processes and specific outcomes without explicit links to how planetary boundaries are addressed. This paper discusses links between sustainable entrepreneurship and the planetary boundaries concept by addressing both perspectives: How can the concept of planetary boundaries provide perspectives for designing and assessing sustainable entrepreneurship? And how can sustainable entrepreneurship contribute effectively to an economy and society operating in a safe operating space for humanity?
CRIS-Team Scopus Importer:2024-06-28
Keywords: Corporate sustainability; Ecopreneurship; Environmental entrepreneurship; Environmental solutions; Planetary boundaries; Safe operating space; Sustainability transformation; Sustainable entrepreneurship; Transition